Switched Boost-Ultra Sparse Matrix Converter - Raghuram M.; Kumar A.; Siva V.; Singh S.K. (My University, 2025)
Incorporation of impedance (Z) source network within ultra sparse matrix converter (USMC) overcomes the limited range of output voltage, load power factor and dynamic load changes. Using this approach, various topologies such as cascaded Z source-ultra sparse matrix converter (ZS-USMC), quasi Z source-ultra sparse matrix converter (QZ-USMC) and series Z source-ultra sparse matrix converter (SZ-USMC) are reported in literature. This paper proposes a new topology which produces same gain and functionality but with less number of passive elements. In addition, in this paper switching strategy of proposed converter is discussed and steady state analysis is also presented. MATLAB simulation is preformed on proposed converter to show the effectiveness of the converter. © 2022 IEEE.